Tourism : the business of travel - Cook, Roy A.; Yale, Laura J.; Marqua, Joseph J. (Upper Saddle River, N.J : Prentice Hall, 1999)
The traveling public and tourism promoters. Tourism service suppliers. The service and hospitality environment.
Keywords: Tourism; Tourism